DERMATOSES IN THE EARLY NEONATAL PERIOD: THEIR ASSOCIATION WITH NEONATAL, OBSTETRIC AND DEMOGRAPHIC VARIABLES - Elisa Maria Michels Krüger; Fernanda Sinkos; Julia Feldmann Uhry; Julio Cesar Bezerra De Boni; Cristina Terumi Okamoto; Kátia Sheylla Malta Purin; Renato Nisihara
ABSTRACT Objective: To evaluate the prevalence of neonatal dermatoses in the early neonatal period and to associate them with neonatal, demographic and obstetric variables. Methods: A cross-sectional study with neonates and their respective mothers, who were hospitalized in a public maternity hospital in Curitiba, PR, Brazil. Data collection was performed using information present in the medical records and a physical examination of the newborn during the period between April 2015 and May 2016. Results: 350 neonates were evaluated. 54.8% were male, and 94.8% (332/350) presented a dermatosis. Among them, 84.6% had, concomitantly, two or more dermatoses. A total of 23 types of dermatoses were diagnosed. The most prevalent were: sebaceous hyperplasia (66%); fluff (42.6%); and salmon patches (41.4%). The mean age of the mothers was 24.9±4.9 years old, and they were predominately white (57.7%). Vernix caseosa was associated with the female gender (p=0.034). Nonwhite mothers were associated with genital hyperpigmentation (p=0.03) and Mongolian spots (p=0.001). Physiological flaking was associated with cesarean deliveries (p=0.03) and a gestational age of over 40 weeks (p=0.054). Salmon patches was associated with primiparity (p=0.0001). Conclusions: There was a high prevalence of neonatal dermatosis in the studied population. Each newborn had, on average, three different dermatoses. Dermatosis in neonates was associated with primiparity, nonwhites, a gestational age of over 40 weeks, and the sex of the newborn.